The Importance of Pedagogical and Social School Climate to Bullying: A Cross‐Sectional Multilevel Study of 94 Swedish Schools. (12th January 2021) - Hultin, Hanna; Ferrer‐Wreder, Laura; Engström, Karin; Andersson, Filip; Galanti, Maria Rosaria
ABSTRACT: BACKGROUND: Bullying is a public health issue with long‐term effects for victims. This study investigated if there was an association between pedagogical and social school climate and student‐reported bullying victimization, which dimensions of pedagogical and social school climate were associated with bullying, and if these associations were modified by individual‐level social factors. METHODS: The study had a cross‐sectional multilevel design with individual‐level data on bullying from 3311 students nested in 94 schools over 3 consecutive school years. School climate was measured with student and teacher questionnaires, aggregated at the school level. The association between school climate and bullying victimization was estimated with multilevel mixed‐model logistic regression. RESULTS: In schools with the most favorable school climate, fewer students reported being bullied. This was especially evident when school climate was measured with the student instrument. Students in schools with favorable climate had an adjusted odds ratio of bullying of 0.74 (95% CI: 0.55‐1.00) compared to students in schools with the worst climate. Results from the teacher instrument were in the same direction, but less consistent. CONCLUSIONS: Improvement in school climate has the potential to affect students both academically, and socially, as well as decrease the prevalence of bullying.